1990
DOI: 10.1128/jvi.64.7.3417-3426.1990
|View full text |Cite
|
Sign up to set email alerts
|

A herpes simplex virus type 1 latency-associated transcript mutant reactivates with normal kinetics from latent infection

Abstract: The herpes simplex virus type 1 (HSV-1) latency-associated transcripts (LATs) accumulate in neuronal nuclei of latently infected ganglia. Explant reactivation kinetics of LAT deletion mutants in the mouse eye model have suggested a role for the LATs in the reactivation process. This report describes the construction and characterization of an HSV-1 strain HFEM mutant, TB1, disrupted within both copies of the LAT gene. TB1 contains a 440-base-pair segment of bacteriophage lambda DNA in place of a 168-base-pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…The TB1 mutation consists of a deletion and insertion of foreign DNA in the middle of the 2-kb LAT sequence. Surprisingly, no 2-kb LAT can be detected in TB1-infected cells or latently infected murine trigeminal ganglia (4).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The TB1 mutation consists of a deletion and insertion of foreign DNA in the middle of the 2-kb LAT sequence. Surprisingly, no 2-kb LAT can be detected in TB1-infected cells or latently infected murine trigeminal ganglia (4).…”
Section: Discussionmentioning
confidence: 93%
“…However, the 2-kb LAT is replaced by smaller introns, the farthest 3Ј of which can be detected by Northern blot analysis (4). It was previously postulated that this RNA arose from a promoter activity lying within the lambda DNA insert (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was first reported by Leib et al (150), who showed that fewer trigeminal ganglia explanted following latent infection with a mutant of the KOS strain of HSV-1 in which the latent phase promoter was specifically deleted were able to produce virus than were control ganglia latently infected with wt virus. Mutants of the 17syn ϩ strain of HSV-1 showed similar reduced and/or delayed recovery levels from latently infected murine dorsal root and trigeminal ganglia (15,56,275). Despite this, Izumi et al (119) and Devi-Rao et al (56) did not see such a delay or reduction in virus recovery from spinal ganglia latently infected with several KOS(M) derived LAT-negative mutants.…”
Section: Latent Phase Transcription Facilitates But Is Not Required Fmentioning
confidence: 97%